Accessing the Stapedius Muscle Via Novel Surgical Retrofacial Approach: A Cadaveric Feasibility Study. Issue 2 (February 2022) - Arnold, Dirk; Schneider, Fritz; Volk, Gerd Fabian; Ossmann, Steffen; Neudert, Marcus; Hirt, Bernhard; Löwenheim, Hubert; Guntinas-Lichius, Orlando
Abstract : Hypothesis: Despite the complete embodiment of the stapedius muscle (SM) into the pyramidal eminence, it is possible to safely gain access to the SM belly via a retrofacial approach. This presents a novel approach to directly measure the electrically evoked stapedius reflex threshold (eSRT). Background: Objective fitting of maximum comfortable loudness levels for cochlear implant users can improve the benefit introduced by the device. Sensing SM activity via direct surgical access represents a potential tool for objective eSRT fitting. Methods: Eighteen human temporal bones (TBs) were used. Micro-computed tomography was performed for six TBs. Standard computed tomography for six TBs. Manual 3D-segmentation of the relevant middle and inner ear anatomy was performed on 12 TBs. Mastoidectomy and posterior tympanotomy allowed the access to middle ear of all 18 the TBs. Once identified the mastoidal segment of the facial nerve (FN), the retrofacial access to the SM was drilled. Results: The total access rate was 72.2%. Only in the first three cases the posterior semi-circular canal was hit. The SM access was identified posterior to the FN at a 4 ± 0.78 mm distance from the stapes' head, almost halfway to the chorda tympani's branching point along the FN direction. The drilling depth to access the SM posterior to the external surface of FN on average was 2 ± 0.30 mm. The exposure took on average of 5 to 8 minutes. Conclusions: The retrofacial approach seems to offer a feasible and reproducible access to the SM belly opening an avenue to electromyographic sensing of eSRT. Abstract : Supplemental Digital Content is available in the text